Cervical Cancer Awareness: An Information Dissemination Campaign In Indonesia - Dedeh Sri Rahayu; Marcos Ochoa (Faculty of Nursing Universitas Padjadjaran, 2015)
This descriptive-correlational study was conducted to determine the level of cervical cancer awareness of 196 participants who were conveniently recruited from selected regions in South Cimahi, Melong, West Java,Indonesia. The survey was conducted on February 2014 for fifteen (15) days using a survey questionnaire for data collection. Descriptive statistics such as frequency and percentage distribution were used for demographic profile and weighted mean for the assessment of the level of awareness on cervical cancer, and inferential statistics such as Pearson r and chi square for hypothesis testing. They have moderate awareness on basic information on cervical cancer, foremost are the areas on prevention, anatomy, treatment and common diagnostic examination, but with very little knowledge or partial awareness on the items pertaining to signs and symptoms, etiology and mode of transmission of cervical cancer. The results of chi square and pearson r tests found that the participants’ gender and educational attainment were not significantly correlated with their level of awareness on cervical cancer while, family monthly income was significantly correlated to their level of awareness. Hence, this study concluded that gender and educational attainment do not necessarily determine a person’s level of awareness or knowledge but family income could contribute to their level of awareness. The study findings formed the basis of designing an information dissemination campaign material on cervical cancer among the residents of South Cimahi, Indonesia. In this regard, an intensive information dissemination campaign program on cervical cancer is recommended using the proposed campaign material designed.Key words: Campaign, cervical cancer, detection, dissemination. Kampanye di Indonesia: Deteksi Dini Kanker Serviks AbstrakPenelitian deskriptif-korelasional ini dilakukan untuk mengetahui tingkat kesadaran 196 peserta yang nyaman direkrut dari daerah tertentu di Cimahi Selatan, Melong, Jawa Barat, Indonesia. Pengumpulan data menggunakan kuesioner. Statistik deskriptif digunakan untuk profil demografis dan rata-rata untuk penilaian tingkat kesadaran mengenai kanker serviks, dan statistik inferensi seperti Pearson r dan Chi square untuk pengujian hipotesis. Hasil penelitian menunjukkan bahwa responden memiliki kesadaran moderat pada informasi dasar tentang kanker serviks, terutama adalah daerah tentang pencegahan, anatomi, pengobatan dan pemeriksaan diagnostik umum, tetapi dengan sedikit pengetahuan atau kesadaran parsial pada item yang berkaitan dengan tanda- tanda dan gejala, etiologi dan cara penularan kanker serviks. Kemudian ditunjukkan bahwa gender dan pendidikan pencapaian peserta tidak signifikan berkorelasi dengan tingkat kesadaran pada saat kanker serviks, pendapatan bulanan keluarga secara signifikan berhubungan dengan tingkat kesadaran. Penelitian ini menyimpulkan bahwa gender dan pencapaian pendidikan tidak selalu menentukan tingkat kesadaran seseorang atau pengetahuan tetapi pendapatan keluarga dapat memberikan kontribusi untuk tingkat kesadaran.Kata kunci: Deteksi, disseminasi, kampanye, kanker serviks.